Capturing Relightable Human Performances under General Uncontrolled Illumination. (6th May 2013) - Li, Guannan; Wu, Chenglei; Stoll, Carsten; Liu, Yebin; Varanasi, Kiran; Dai, Qionghai; Theobalt, Christian
Abstract: We present a novel approach to create relightable free‐viewpoint human performances from multi‐view video recorded under general uncontrolled and uncalibated illumination. We first capture a multi‐view sequence of an actor wearing arbitrary apparel and reconstruct a spatio‐temporal coherent coarse 3D model of the performance using a marker‐less tracking approach. Using these coarse reconstructions, we estimate the low‐frequency component of the illumination in a spherical harmonics (SH) basis as well as the diffuse reflectance, and then utilize them to estimate the dynamic geometry detail of human actors based on shading cues. Given the high‐quality time‐varying geometry, the estimated illumination is extended to the all‐frequency domain by re‐estimating it in the wavelet basis. Finally, the high‐quality all‐frequency illumination is utilized to reconstruct the spatially‐varying BRDF of the surface. The recovered time‐varying surface geometry and spatially‐varying non‐Lambertian reflectance allow us to generate high‐quality model‐based free view‐point videos of the actor under novel illumination conditions. Our method enables plausible reconstruction of relightable dynamic scene models without a complex controlled lighting apparatus, and opens up a path towards relightable performance capture in less constrained environments and using less complex acquisition setups.